Digital Citizenship in Schools : Nine Elements All Students Should Know - Ribble, Mike (Book collections on Project MUSE., 2015)
Explains the relevance and importance of digital citizenship and explores its elements. Provides lesson plans and professional development activities to help educators determine how to go about incorporating digital citizenship concepts into the classroom.